2011
DOI: 10.1111/j.1365-2109.2011.02838.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low salinity on microbial floc composition and performance of Litopenaeus vannamei (Boone) juveniles reared in a zero-water-exchange super-intensive system

Abstract: This study aimed to evaluate the e¡ect of low salinity on the water quality, microbial £ocs composition and performance of Litopenaeus vannamei juveniles reared over 40 days in a zero-water-exchange super-intensive system at 0, 2, 4 and 25 g L À 1 . At 0 g L À 1 , the mortality was total at the 26th day, and consequently, these salinity data were not included in the statistical analysis. Among the water quality parameters, only pH and the total suspended solids concentration were signi¢cantly in£uenced by sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 28 publications
11
48
3
3
Order By: Relevance
“…Although the differences were not statistically significant, the results were informative because the weight gain attained at 4‰ (coefficient of variation 0.40) salinity was almost half of that obtained at 32‰ (coefficient of variation 0.16). Laramore et al (2001), Walker et al (2009), andMaicá et al (2012), also in a system without water exchange, likewise recorded higher weight gains for both L. vannamei postlarvae and juveniles maintained at high salinity (at 30, 28 and 25‰, respectively), than at low salinity (at 4, 2 and 2‰, respectively). Furthermore, Perez-Velazquez et al (2012) reported a reduced value of weight gain of the referred species post-larvae reared in a water temperature of 24 ºC, at salinity of 4‰ and with a Na + :K + ratio of 120 (514.0%), compared with that of 40 (1,212.8%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the differences were not statistically significant, the results were informative because the weight gain attained at 4‰ (coefficient of variation 0.40) salinity was almost half of that obtained at 32‰ (coefficient of variation 0.16). Laramore et al (2001), Walker et al (2009), andMaicá et al (2012), also in a system without water exchange, likewise recorded higher weight gains for both L. vannamei postlarvae and juveniles maintained at high salinity (at 30, 28 and 25‰, respectively), than at low salinity (at 4, 2 and 2‰, respectively). Furthermore, Perez-Velazquez et al (2012) reported a reduced value of weight gain of the referred species post-larvae reared in a water temperature of 24 ºC, at salinity of 4‰ and with a Na + :K + ratio of 120 (514.0%), compared with that of 40 (1,212.8%).…”
Section: Discussionmentioning
confidence: 95%
“…In this study, shrimp survival was significantly affected by salinity, with increasing mortality as the salinity decreased from 32 to 16 and 4‰. Similar effects were reported by Laramore et al (2001) with L. vannamei post-larvae at salinities of 4 and 30‰ (survival of 86 and 100%, respectively); Jayasankar et al (2009), with post-larvae at salinities of 0.0, 0.5, 0.75 and 1.5‰ (survival of 2, 29, 47 and 85%, respectively) and juveniles at salinities of 0.0, 0.5 and 0.75‰ (survival of 65, 77 and 93%, respectively); Decamp et al (2003), with juveniles, in a system without water exchange, at salinities of 9, 18 and 36‰ (survival of 68, 93 and 94%, respectively); and Maicá et al (2012), with juveniles, in the same system, at salinities of 2, 4 and 25‰ (survival of 22.50, 72.73 and 97.50%, respectively). Moreover, Perez-Velazquez et al (2012) observed a reduced value of survival of L. vannamei post-larvae reared at a water temperature of 24 ºC, at a salinity level of 4‰ and with a Na + :K + ratio of 120 (10.0%), compared with the 40 (95%).…”
Section: Discussionmentioning
confidence: 99%
“…O sistema de microcosmo manteve as variáveis físico-químicas basicamente idênticas para todos os tratamentos e dentro da faixa recomendada para o cultivo da espécie (Van Wyk & Scarpa, 1999;Lin & Chen, 2001Decamp et al, 2007;Avnimelech, 2009;Furtado et al, 2011;Gaona et al, 2011;Maicá et al, 2012). Portanto o sistema de recirculação, baseado no esquema proposto por Moss & Moss (2004), mostrou-se eficiente para separar os efeitos do estresse populacional e da degradação da qualidade da água, sobre o desempenho dos camarões, em razão do aumento populacional.…”
Section: Resultsunclassified
“…The physicochemical parameters also affect the microalgae dominance. Maicá et al [52] observed in a L. vannamei biofloc culture greater abundance of chlorophytes in salinity of 2 %, while in 25 % diatoms were the most abundant.…”
Section: Microalgaementioning
confidence: 99%
“…Maicá et al [52] found an average concentration of 164, 64, and 29 ciliates mL −1 in water salinities of 2%, 4%, and 25%, respectively. Furthermore, Monroy-Dosta et al [40] observed minimum and maximum concentrations of 13 and 39 and also noted a variation in species according to the culture age.…”
Section: Zooplanktonmentioning
confidence: 99%